THE MEDICAL TRADITIONS OF INDONESIAN- OSING- ETHNIC: TYPES OF LEXICAL MEANING OF TREAT VERB IN OSING LANGUAGES: TRADISI PENGOBATAN ETNIK OSING-INDONESIA: TIPE-TIPE MAKNA LEKSIKAL VERBA MENGOBATI DALAM BAHASA OSING - Asrumi Asrumi; Agus Sariono; Anastasia Erna Rochiati Sudarmaningtyas; Edy Hariyadi; Agustina Dewi Setyari (LLDIKTI Wilayah X, 2022)
The purpose of this study is to reveal the types of lexical verbs that mean